Finance and Inclusive Human Development: Evidence from Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
This study investigates direct and indirect linkages between financial development and inclusive human development in data panels for African countries using a battery of estimation techniques, notably: Two-Stage Least Squares, Fixed Effects, Generalized Method of Moments and Tobit regressions. The dependent variable is the inequality adjusted human development index. All dimensions of the Financial Development and Structure Database (FDSD) of the World Bank are considered. The main finding is that financial dynamics of depth, activity and size improve inclusive human development, whereas the inability of banks to transform mobilized deposits into credit for financial access negatively affects inclusive human development. Policy implications are discussed in the light of fighting surplus liquidity and providing information sharing offices (like public credit registries and private credit bureaus) that would reduce information asymmetry between lenders and borrowers.
Keywords: E00; G20; I00; O10; 330; Banking; human development; Africa